Causal Theories of Knowledge : Why They Leave Gettier Problems Unresolved. - Dierich, Chris (My University, 2009)
Philosophers have been interested in what constitutes Knowledge for centuries. The claim Knowledge=Justified True Belief can be traced back as far as Plato. With the use of a few examples Edmund Gettier showed that JTB is necessary but not sufficient for knowledge. Alvin Goldman tries to address this by requiring that there be a causal connection between the fact that makes something true and the person knowing it. Because inductive reasoning plays a crucial role in the formation of knowledge, we will suggest that theories with causal elements are subject to criticism.
A Critique of the Causal Theory of Knowledge.
Color poster with text and diagrams (Spring 2009)
Keywords: Gettier problem; Knowledge, Theory of; Posters